MANEJO NUTRICIONAL NA FIBROSE CÍSTICA (REMUNOM, 2024)
The present study aims to present the main characteristics of Cystic Fibrosis as well as the importance of nutritional management to increase its stability and patient survival.  Cystic Fibrosis is a genetic, chronic, lethal disease that is more common in white people.  It occurs due to the mutation of the CFTR (Cystic Fibrosis Transmembrane Conductance Regulator) gene, which produces a defective protein of the same name, causing body fluids to become viscous and thick, mainly affecting the lungs, pancreas and digestive system.  The nutritionist is an extremely important professional and allied to the treatment of Cystic Fibrosis, since adequate nutrition is correlated with better lung function, the treatment and prevention of malnutrition which is common among those affected, aiming to achieve and maintain the ideal weight, adapt energy and macro and micronutrient intake, as well as reducing their malabsorption.  The study is research based on a qualitative and descriptive bibliographical survey, through books, informative articles and publications in scientific databases.